Evaluation of most influential factors affecting road traffic accidents in Sidon, Lebanon - Karim, Faisal; Ali, Shaban Ismael Albrk (Penerbit Universiti Kebangsaan Malaysia, 2020)
Enlargement of the transportation industry in developing countries has had a tremendous impact on the advancement of those countries. This advancement has had both positive and negative impacts on society. Drawbacks primarily include the emission of harmful gases from vehicles, traffic overcrowding, and most importantly, injuries, and deaths by traffic accidents, which have increased significantly. This paper focuses on and investigates the human, vehicle and environmental factors affecting road traffic accidents in Lebanon in order to increase the knowledge surrounding how the elements have impacted the increase in accidents in Lebanon. A quantitative method (questionnaire) was used to collect data to understand the behavior of road users, while the relative importance index (RII) was used to analyze the data. The results illustrate that the top three vehicle-related factors that lead to an increase in the accidents in Lebanon according to the respondents are steering wheel defects with an RII of 3.807, mechanical faults with an RII of 3.489 and 2.934 for lack of vehicles among all the groups. Furthermore, the human factors were recognized to have a slight impact on road traffic accidents with the highest RII of 1.719 for failure to follow driving codes. In conclusion, a country’s development not only depends on economic measure, but it is also determined based on how effective the traffic system infrastructure is and the steps taken to minimize injuries.